Bimbingan Belajar untuk Meningkatkan Prestasi Belajar di Tenjo - Nababan, Ernie Bertha; Dirgantoro, Kurnia Putri Sepdikasari; Rahmadi, Pitaya; Listiani, Tanti; Pardamean Sinaga, Darma Roh (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Abstract The transition from online learning to offline learning still affects students' learning adaptation. Students' learning adaptation does not go smoothly in face-to-face learning. The impact of online learning has made students accustomed to studying on their own, and some students stop learning when they cannot complete their assignments. This leads to low understanding and motivation among students. Low motivation requires learning support to enhance students' learning achievements, which can be observed through their report card grades. Tenjo tutoring services aim to provide learning support for students. Tenjo tutoring accompanies each student through tutors who come every Saturday and teach students in their respective grade levels. The students who receive tutoring and guidance range from grades 3, 4, 5, and 6 in elementary school to grades 7, 8, and 9 in junior high school. The tutoring program lasts for approximately one year, from August 2022 to May 2023. Based on interviews with the person in charge of Tenjo who directly interacts with the students' parents, it is reported that Tenjo tutoring has greatly helped their children's learning. Students' learning achievements have shown improvement, as indicated by the increase in their report card grades. Keywords: Learning Achievement, Tenjo, GKI Gading Serpong